2000
DOI: 10.1046/j.1523-1755.2000.t01-1-00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-induced growth of vascular smooth muscle cells requires an Src-dependent activation of the epidermal growth factor receptor

Abstract: Our data suggest that EGFR serves as a role in mitogenic signaling following stimulation with Ang I through a ligand-independent and Src-dependent transactivation of the EGFR. Furthermore, we demonstrate this transactivation as a pivotal step in Ang II-induced activation of MAP kinase and PI3 kinase, as well as growth of VSMCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 27 publications
6
69
0
1
Order By: Relevance
“…Early in 2001, EI Mabrouk et al demonstrated that ERK1/2 phosphorylation is dose dependently increased by Ang II in VSMCs from spontaneously hypertensive (SHR) and Wistar-Kyoto (WKY) rats, and the ERK1/2 inhibitor PD-98059 can block Ang IIinduced VSMC growth [21] . In VSMCs, Ang II type I receptorinduced ERK1/2 activation occurs via Ca 2+ and Src-dependent transactivation of the EGFR [33,34] . Ang II can activate ERK1/2 by the Ras/PKCzeta/MEK pathway in VSMC [35] .…”
Section: Discussionmentioning
confidence: 99%
“…Early in 2001, EI Mabrouk et al demonstrated that ERK1/2 phosphorylation is dose dependently increased by Ang II in VSMCs from spontaneously hypertensive (SHR) and Wistar-Kyoto (WKY) rats, and the ERK1/2 inhibitor PD-98059 can block Ang IIinduced VSMC growth [21] . In VSMCs, Ang II type I receptorinduced ERK1/2 activation occurs via Ca 2+ and Src-dependent transactivation of the EGFR [33,34] . Ang II can activate ERK1/2 by the Ras/PKCzeta/MEK pathway in VSMC [35] .…”
Section: Discussionmentioning
confidence: 99%
“…These findings with Ang II were surprising in light of data from cultured VSMCs isolated from large arteries, which indicated an important role of EGFR transactivation in Ang II-induced ERK1/2 signaling and growth. 28 Several groups have demonstrated that EGFR transactivation is mediated by membrane shedding of HB-EGF, 20,29 and in mesangial cells, Ang II-induced HB-EGF shedding and EGFR transactivation was blocked by the MMP inhibitor batimastat. 30 Recently, Hao et al 18 have shown by use of large mesenteric arteries that ␣ 1b -adrenoreceptor-induced contraction involved MMP-7 and EGFR transactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Several GPCR agonists stimulate EGF-R transactivation, including lysophosphatidic acid, thrombin (2,25), ANG II (14,37), arginine vasopressin (19), and ET-1 (10). More recently, a novel mechanism of EGF-R transactivation has been proposed whereby GPCR-mediated activation of Src, PYK2, and Ca 2ϩ mobilization leads to a metalloprotease proteolytic cleavage of the pro-heparinbinding (HB)-EGF precursor to yield the release of a mature ligand, which in turn activates the EGF-R (9, 32).…”
mentioning
confidence: 99%